2021
DOI: 10.1161/circoutcomes.120.007230
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding Risk of Direct Oral Anticoagulants in Patients With Heart Failure And Atrial Fibrillation

Abstract: Background: Patients with heart failure and atrial fibrillation are an important atrial fibrillation subgroup in which direct oral anticoagulants (DOACs) have not been adequately studied in real-world settings. Since DOACs rely on renal elimination and renal dysfunction is prevalent in patients with heart failure, their use may increase bleeding risk, negating some of their advantage over warfarin. Methods: We conducted a retrospective cohort study usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
0
15
0
1
Order By: Relevance
“…FXIa inhibitors have the potential to improve the benefit/risk profile of existing anticoagulants by reducing thrombus formation without causing an increase in bleeding [ 13 20 ]. There is additional unmet need for safer anticoagulants in renal impairment patients with concomitant cardiovascular disease as these patients have a higher intrinsic risk of bleeding [ 39 ], and this risk may further increase with currently available anticoagulants [ 36 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FXIa inhibitors have the potential to improve the benefit/risk profile of existing anticoagulants by reducing thrombus formation without causing an increase in bleeding [ 13 20 ]. There is additional unmet need for safer anticoagulants in renal impairment patients with concomitant cardiovascular disease as these patients have a higher intrinsic risk of bleeding [ 39 ], and this risk may further increase with currently available anticoagulants [ 36 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with renal impairment are at heightened risk of bleeding when taking anticoagulant therapies [ 35 ]; however, it is unknown if this is purely due to increases in drug exposure, intrinsic features of this patient population, or a combination of both [ 36 38 ]. The increased risk of bleeding in patients with renal impairment has been observed even without anticoagulant therapies, with one study demonstrating a 1.5-fold increased risk of bleeding in patients with chronic kidney disease compared with those without chronic kidney disease [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is well-known that patients with heart failure have a high prevalence of renal dysfunction [ 22 ]. Since all NOACs are renally eliminated to various degrees while warfarin is not, progressive renal function decline leads to an increased risk of bleeding in the treatment of NOAC [ 24 , 25 ]. However, in our study there was only one patient with renal dysfunction (according to the criteria of the HAS-BLED scale).…”
Section: Discussionmentioning
confidence: 99%
“…When analyzing the DOAC and NSAIDs drug exposure, our study showed higher rates than other observational studies but similar to the ARISTOTLE trial (8.2%). 9,26,39,43 We must consider that NSAIDs can be used almost worldwide as overthe-counter (OTC) medications. Given that OTC medication use is not well documented, thus the exposure can be underestimated.…”
Section: Discussionmentioning
confidence: 99%